Fixed-target serial femtosecond crystallography using in cellulo grown microcrystals. (2021) - Lahey-Rudolph, J. Mia; Scho¨nherr, Robert; Barthelmess, Miriam; Fischer, Pontus; Seuring, Carolin; Wagner, Armin; Meentsb, Alke; Redecke, Lars
No abstract available